نمذجة محولات التحكم بزاوية الطور واستخداماتها - الفقيه, نبيل; الخطيب, محمد (Latakia University Journal -Engineering Sciences Series, 2018)
يعد استخدام محولات التحكم بزاوية الطور PST)) ضرورة ملحة في الشبكات الكهربائية التي يتم العمل على تحسين مردودها لأنها تتيح التحكم بسريان الاستطاعة في خطوط الشبكة بما يفيد في تقليل الضياعات. تعد PST تقانة ناضجة يستخدمها مشغلو شبكة النقل الكهربائية فهي تقدم حلاً متكاملاً للتحكم بسريان الاستطاعة يتصف بالوثوقية العالية والاقتصادية. تم في هذا البحث التعرض إلى تصنيف محولات التحكم بزاوية الطور واستخداماتها، كما تم اقتراح نموذج حاسوبي يتسم بالبساطة دون الخوض في تفاصيل التحكم في هذا المحول، حيث يعطي النموذج المقترح نتائج استخدام هذا المحول عن طريق تمثيل توتر الإزاحة بالطور وقد تم تمثيل هذا النموذج على برنامج Matlab/Simulink اعتماداً على النموذج الرياضي الذي تم بناؤه في بيئةmatlab أصبح لدينا نموذجاً مقترحاً يبين أثر هذا المحول عن طريق تمثيل التوتر على خرجه وقد تم التحقق من النتائج باستخدام برنامج neplan وذلك بدراسة حالة بينت دور هذا النوع من المحولات في التحكم بسريان الاستطاعة والآثار الإيجابية على الشبكة المتمثلة في تحسين التوتر وتقليل الضياعات. Phase Shifting Transformer has played an important role in electrical networks to improve their efficiency because it has the ability to control power flow in electrical transmission network that can lead to power loss minimization. PST technology is considered as mature technology which is used by transmission system operators. These transformers provide an integrated solution to control power due to the advantages of low economic and high reliability. In this research an exposure to the classification of phase shifting transformers and their application then a simple model for Phase shifting transformer is suggested without seeking in the details of transformer, this model presents the result for using PST via modeling phase shifting voltage, this model is performed using Matlab/Simulink program according to differential equation. Depending on the mathematical model which has been built in an Matlab environment we have a model shows the impact of this transformer through the representation of output voltage , results are verified using Neplan program via a case study demonstrated the role of this type of transformers in controlling power flow in transmission system achieving remarkable power loss reduction and improving voltage profile